2012
DOI: 10.1080/0309877x.2011.614932
|View full text |Cite
|
Sign up to set email alerts
|

A transnational comparison of lecturer self-efficacy

Abstract: Benchmarking within higher education is now relatively commonplace, as institutions increasingly compete directly with one another to improve the overall 'quality' of what they do and attempt to establish and better their position among peers as measured against sector standards. The benchmarking of confidence among academic staff in relation to the skills associated with teaching, research and service tasks, at least as far as these three core functions are traditionally conceived and understood, is, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…pressure to publish). Support for this specific finding can be found in recent work conducted in Australia (Hemmings & Kay, 2010a, 2010b and the UK (Hemmings, Kay, Sharp, & Taylor, 2012;Sharp, Hemmings, Kay, & Callinan, 2012) where research self-efficacy, that is, an individual's confidence to successfully perform tasks when conducting research (Forester, Kahn, & HessonMcInnis, 2004), proved to be the most potent predictor, amongst several other factors, of research output. Again, these studies drew on quantitative data obtained from mail-out surveys.…”
Section: Literature Reviewsupporting
confidence: 57%
See 2 more Smart Citations
“…pressure to publish). Support for this specific finding can be found in recent work conducted in Australia (Hemmings & Kay, 2010a, 2010b and the UK (Hemmings, Kay, Sharp, & Taylor, 2012;Sharp, Hemmings, Kay, & Callinan, 2012) where research self-efficacy, that is, an individual's confidence to successfully perform tasks when conducting research (Forester, Kahn, & HessonMcInnis, 2004), proved to be the most potent predictor, amongst several other factors, of research output. Again, these studies drew on quantitative data obtained from mail-out surveys.…”
Section: Literature Reviewsupporting
confidence: 57%
“…To exemplify, there have been a number of studies investigating how gender has interacted with research self-efficacy. Zhao, McCormick, and Hoekman (2008) and Hemmings et al (2012), using survey methods, have identified lower levels of self-efficacy for research in female academics compared with their male counterparts. In terms of qualifications, researchers such as Bailey (1999), Hemmings et al (2012) and Quimbo and Sulabo (2014) have reported that those faculty members with doctoral qualifications tend to be more self-efficacious with respect to research and also invest greater time to research endeavours.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Self-efficacy has long been found to be a strong predictor of performance outcomes across academic populations over and above the effects of prior achievement, including K-12, undergraduate, and graduate students (e.g., for reviews, see [22–23]) as well as K-12 teachers [24]. With respect to post-secondary faculty, international research over the past three decades has also explored this social-cognitive construct as reflective of faculty beliefs in their ability to teach (e.g., The Netherlands [25]; China [26]), conduct research (e.g., Turkey [27]; U.S. [28]), and engage in service (e.g., public outreach among U.S. faculty [29–30]), among other academic activities (e.g., administration and consulting, Australia [31]; computing, Nigeria [32]; see also [33]).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to findings on teaching self-efficacy among K-12 educators [39], existing research has also shown faculty self-efficacy beliefs for research to be higher among senior relative to junior faculty members [31,36]. Prior studies have further examined faculty self-efficacy beliefs specific to a given discipline (e.g., STEM [30]; foreign language instruction [27,35]), with scattered findings showing faculty self-efficacy levels to be more problematic in specific disciplines relative to others (e.g., education [33]; social sciences [26]; accounting [31]).…”
Section: Introductionmentioning
confidence: 99%